Integrating intensive interaction developing communication practice in services for children and adults with severe learning difficulties, profound and multiple learning difficulties and autism - Mouriere, Amandine; McKim, Jules (Routledge, 2018)
"This unique book features a collection of lively stories on the integration of Intensive Interaction practice into schools and adult service settings. It addresses communication development both from a micro and macro level across a variety of service settings, with each chapter written by a different practitioner. These personal accounts cover individual practice and reflection with a single case-study person, as well as influencing organisational change. The authors assert that, within adult services and educational settings, Intensive Interaction can be used as a way to develop communication and confidence and to work with the principles of inclusion and person-centred acceptance and support. The book develops an understanding of issues that can be addressed within training and mentoring other staff, and uses case studies throughout as a powerful training tool" --Provided by publisher.